(untitled) (Journal of Partial Differential Equations, 1997)
To following boundary value problem a(t)Φ^+(t) + b(t)Φ^+[α(t)] + c(t)Φ^-(t) + d(t)Φ^-[a(t)] = f(t) this paper has given out the number of linearly independent solutions and the conditions of solvability, so as to deepen the study of the problem to the same level as that of following problem a(t)Φ^+(t) + b(t)Φ^+(t) + c(t)Φ^-(t) + d(t)Φ^-(t) = f(t)